"Completing Europe's Economic and Monetary Union": Any support from the citizens? - Francesco Farina; Roberto Tamborini (Kiel Institute for the World Economy (IfW), 2016)
The aim of the 'Five Presidents Report' cited in the title acknowledges that an important driver of the European economic crisis has been the faulty original design of the Monetary Union, and that substantial steps are urgently needed towards the creation of truly supranational institutions. Yet economists tend to neglect that however compelling economic analyses may be, the stumbling block on the way of the reform of the Monetary Union is political will, and that in democracies the ultimate source of political will comes from electors. In this paper, first of all the authors wish to bring to the economists' attention some recent analyses of citizens' attitudes towards Europe from political science. Then, by cross-referencing the results of the 2014 elections of the European Parliament with Eurobarometer opinion polls eliciting judgements for the EU vis-à-vis home countries and an indicator of economic pain, they show the presence of a geo-economicpolitical cleavage across four groups of countries. This is more complex, and perhaps worse, than the simplistic divide between 'North' and 'South' or 'Core' and 'Periphery'. The main implication is that the EU experiences a stalemate between 'more Europe vs. less Europe' at the level of peoples, which seriously undermines support for further integration 'from below'.
Keywords: E02; E42; 330; European Economic and Monetary Union; economic crisis; European integration; Eurobarometer opinion polls; 2014 elections of the European Parliament